Is the Barnabas Document a Proponent of a Trinitarian or Hierarchical (Subordinate) Divine Concept? - Nagel, Peter (Neotestamentica, 2025)
The Barnabas document was a popular text among a few early Christian communities. Together with the Shepherd of Hermas, it forms part of one of the most important Christian manuscripts, namely, Codex Sinaiticus, and like the works of Clement and Origen, it too is associated with Alexandria. The document offers insight into how early Christians, in a second-century Egyptian context, thought about divinities, in particular the Judeo-Christian deity, Jesus, and the Pneuma, and how they relate. This leads to questions relating to the trinitarian theology of the document, and whether there is any at all. The aim of this study is to come to an understanding of how Jesus, the Judean-Christian deity and the Pneumarelate as an attempt to answer the question of whether the Barnabas document is a proponent of a trinitarian or hierarchical (subordinate) divine concept or not. To do this, the study has identified Barn. 5:1-14, 7:1-11, 12:1-12, and the concept "Son of Theos" and "the Pneuma" as the primary focus, parameters, and frame.